RNA Interference of Human Papillomavirus Type 18 E6 and E7 Induces Senescence in HeLa Cells - Hall, Allison H. S. (American Society for Microbiology, 2003)
The human papillomavirus oncoproteins E6 and E7 promote cell proliferation and contribute to carcinogenesis by interfering with the activities of cellular tumor suppressors. We used a small interfering RNA molecule targeting the E7 region of the bicistronic E6 and E7 mRNA to induce RNA interference, thereby reducing expression of E6 and E7 in HeLa cells. RNA interference of E6 and E7 also inhibited cellular DNA synthesis and induced morphological and biochemical changes characteristic of cellular senescence. These results demonstrate that reducing E6 and E7 expression is sufficient to cause HeLa cells to become senescent.